Analytical applications of microbial fuel cells. Part I: Biochemical oxygen demand - Abrevaya, Ximena Celeste (2014)
Microbial fuel cells (MFCs) are bio-electrochemical devices, where usually the anode (but sometimes the cathode, or both) contains microorganisms able to generate and sustain an electrochemical gradient which is used typically to generate electrical power. In the more studied set-up, the anode contains heterotrophic bacteria in anaerobic conditions, capable to oxidize organic molecules releasing protons and electrons, as well as other by-products. Released protons could reach the cathode (through a membrane or not) whereas electrons travel across an external circuit originating an easily measurable direct current flow. MFCs have been proposed fundamentally as electric power producing devices or more recently as hydrogen producing devices. Here we will review the still incipient development of analytical uses of MFCs or related devices or set-ups, in the light of a non-restrictive MFC definition, as promising tools to asset water quality or other measurable parameters. An introduction to biological based analytical methods, including bioassays and biosensors, as well as MFCs design and operating principles, will also be included. Besides, the use of MFCs as biochemical oxygen demand sensors (perhaps the main analytical application of MFCs) is discussed. In a companion review (Part 2), other new analytical applications are reviewed used for toxicity sensors, metabolic sensors, life detectors, and other proposed applications.